“FUN LEARNING” SEBAGAI ALTERNATIF UNTUK MENINGKATKAN MINAT BELAJAR MATEMATIKA SISWA MI TERDAMPAK COVID-19 DI DESA SAWO KABUPATEN GRESIK - Mazidatun Nadhifah Nadhifah; Vina Pandu Winata; Khafidhoh Nurul Aini (INSPIRAMATIKA, 2021)
This research is a descriptive qualitative research, which aims to describe the application of the fun learning method as an alternative to increase students' interest in learning mathematics. The subjects of this research were class II students of MI Nurul Huda, Sawo Village, Gresik Regency, for the 2021/2022 academic year. Determination of the subject is based on the results of the survey or observations of the researcher team. The instruments used in this research are test questions, fun learning implementation guidelines, and student learning interest questionnaires. The research was carried out in a blended manner, namely combining online and offline. The data used are the results of tests, tests and questionnaires of interest in learning mathematics given before and after the application of the fun learning method. Based on the recapitulation and data reduction that has been done, the results of this study indicate that: (1) Grade 2 students of MI Nurul Huda are more active in participating in learning activities in class using the fun learning method, so this method is very appropriate to be an alternative learning method in class, especially in the classroom. math. (2) The results of the questionnaire on students' interest in learning mathematics showed an increase, which means that learning by playing can restore and increase students' interest in learning mathematics. (3) The final test results show an increase in students' understanding and knowledge after the implementation of the fun learning program, which means that students are more enthusiastic about learning. So it can be concluded that by implementing a fun learning program can create a learning atmosphere that is fun and popular with students.